THE TEACHERS’ PERCEPTIONS OF SUPERVISION IN IMPROVING THEIR PROFESSIONAL COMPETENCE AT HIKMATUL SALRIDHO SCHOOL - Dalimunthe, Gilang Luthfie; Ahmad Yudha Pratama; Rambe, Sutan Rizki; Safiraazzahra; Jihan Khairani (CV. Asry Persada Quality, 2024)
This study was conducted to evaluate teachers' views on the effectiveness of supervision conducted by supervisors in an effort to improve their professional competence at Hikmatul Salridho School in Batang Kuis. The method used in this research is a survey with a qualitative approach. The research subjects consisted of teachers representing Hikmatul Salridho school, especially grade 6 teachers. The findings of this study indicate that the teachers have a positive view of the effectiveness of supervision in improving their professional competence at Hikmatul Salridho school. In the implementation of this study, a survey instrument was used to collect data regarding the teachers' views and perceptions of the success of supervision in strengthening and improving their professional competencies. Therefore, it is necessary to have a policy from the education office to carry out supervision to improve professional competence in schools Hikmatul Salridho.